Mewujudkan Guru Agama Hindu Profesional Dengan Spirit Karma Yoga - Ni Komang Rina Yuliasmini (Jayapangus Press, 2019)
To support the realization of the ideals of character development as mandated in Pancasila and the Preamble of the 1945 Constitution and to overcome current national problems, the Government makes character development one of the national development priority programs, as outlined in the National Action Plan for Character Education (2010): character education mentioned as value education, character education, moral education, character education that aims to develop the ability of students to make good decisions, maintain what is good and realize that goodness in everyday life with all their heart .. Character Culture Development and Education Nation). In view of the above, professional teachers are required to have commitment, responsibility, learning from experience, become part of the learning community, so as to improve students' character. The teacher is one of the most important components in realizing the plan. Including Hinduism teachers who have important functions in carrying out forming noble characters. Therefore the increase in teacher qualifications is directed towards becoming professional teachers as mandated in Law R.I. Number 14 of 2005 concerning Teachers and Lecturers. To realize a professional Hindu teacher must be developed by a Hindu religious teacher. 4 These competencies are (1) Paedagogic Competence (2) Social Competence (3) Professional Competence (4) Personality Competence. In the development of the 4 Competencies Teachers Hinduism can use the spirit of karma yoga in the formation of the work ethic